An Analysis of Learning Management of English Course: A Case Study at Star English Course - Rezki Adelya; Zulfah; Abdul Haris Sunubi (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
Educational management is an activity or series of activities in the form of managing the collaborative efforts of a group of people who are part of an educational organization, to achieve pre-established educational goals, by utilizing existing resources and employing management functions to achieve the goals effectively and efficiently. This research is expected to increase the knowledge about learning management in STAR ENGLISH Course Parepare. By analyzing management strategies that implemented in course, this research provides new insight into effective and efficient management practices in non-formal education. This research employs a qualitative descriptive. Data collection techniques include in-depth interviews with director and two senior teachers. Instruments included interview guidelines, observation checklist, and documentation records. Data were analyzed using Miles and Huberman's interactive analysis model, comprising data collection, reduction, display, and conclusion drawing. The findings reveal that the steps in preparing lesson plan at STAR EC include determining the learning objectives, learning strategies, and the materials. organizing process consist of task organization between director, teachers, and staff. In the division of tasks within a class, each class has a main teacher and an assistant teacher or an observant teacher. In the learning process, especially during practice sessions, tutors use a strategy of grouping students based on their abilities. the lesson actuating in star ec begins with the teacher open the class and delivering the material during the first 30 minutes. In the next 30 minutes, the teacher conducts exercise for students using the material that been taught that day. The last 30 minutes are used for playing games and conducting a final test. In learning actuating process in classroom, the teacher faces several challenges and the teachers have their own ways of coping these challenges. Coaching that conducted in SEC is divided into several parts which are holds briefing regularly to ensure teachers’ performance is stay on track in teaching, and evaluate teachers’ performance. And then becoming an observant teacher, moreover monitoring by the director, and asking for feedback. The evaluation for students is generally conducted through two types of tests: formative and summative. Evaluation is also conducted for the teachers, where the director discusses the teacher’s performance with senior teachers. Additionally, students are involved in evaluating teacher by providing their feedback.